2015
DOI: 10.1017/s1368980014003000
|View full text |Cite
|
Sign up to set email alerts
|

Maternal resources and household food security: evidence from Nicaragua

Abstract: Objective: Women (especially mothers) are theorized as critical to reducing household food insecurity through their work and caregiver roles. The present study tests these assumptions, assessing how maternal economic and social resources are associated with food insecurity in households with young children. Design: Data from a population-based sample of households was collected in León, Nicaragua (n 443). Data include a newly validated measure of household food insecurity (ELCSA), maternal resource measures, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
19
1
3
Order By: Relevance
“…Although we did have a measure of partner income, we did not collect information on how much the partners shared this income with the pregnant women. Recent research shows that when women have control over the household spending, household food insecurity is significantly lower (Schmeer et al, 2015). More information regarding resource sharing within this small dyadic network would be helpful to further investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we did have a measure of partner income, we did not collect information on how much the partners shared this income with the pregnant women. Recent research shows that when women have control over the household spending, household food insecurity is significantly lower (Schmeer et al, 2015). More information regarding resource sharing within this small dyadic network would be helpful to further investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the questions do not specifically speak to maternal food insecurity, which possibly have different significant predictors. For example, self-income may have been significant across both studies due to the relationship between monetary funds and maternal food insecurity (Schmeer et al, 2015). Additionally, we may have found the mental health resources to be more consistently significant across the communities based on previous research in high-income countries (Laraia, Siega-Riz, Gundersen, & Dole, 2006; Whitaker, Phillips, & Orzol, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, at least 50% of women, as compared to the total number of participants, have now greater access and control of the family income, due to the sale of those surplus products. Some studies have shown that when women's economic contribution is greater, families are less exposed to food insecurity [43].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, food shortage may have lasted longer than the period of 12 months evaluated in the study and stunting and underweight in these children might have developed before this period, as the authors properly pointed out (10) . In a population-based study, Schmeer et al (11) tested the hypothesis that mothers' economic and social resources can help to reduce FI. Evaluating households with children aged 3-11 years, the authors found a high FI rate (75 %) in a town in Nicaragua.…”
Section: Studies In Low-and Middle-income Countriesmentioning
confidence: 99%